Precision Medicine Powered by pHealth and Connected Health ICBHI 2017, Thessaloniki, Greece, 18-21 November 2017 (IFMBE Proceedings,, 2018)
This volume presents the proceedings of the 3rd ICBHI which took place in Thessaloniki on 18-21 November, 2017.The area of biomedical and health informatics is exploding at all scales. The developments in the areas of medical devices, eHealth and personalized health as enabling factors for the evolution of precision medicine are quickly developing and demand the development of new scaling tools, integration frameworks and methodologies. .